Effect of TUG-BACK on tightness of filling root canal apex - I. O. Larichkin; E. V. Chestnykh; A. I. Ivanova; E. P. Zinkovskaya; I. Yu. Kuritsyna; D. V. Medvedev; N. V. Shedyakova; E. L. Zakharova; M. V. Yusufova; K. V. Kulikova (Эндодонтия Today, 2025)
AIM. To evaluate the effect of tug-back on the apical seal of root canal fillings. MATERIALS AND METHODS. Root canal treatment and filling were performed in 20 removed single-root teeth. The teeth were divided into 2 groups, with and without the tug-back effect. The cuts were made at the level of 1 and 3 millimeters from the apical constriction. The microstructure of the samples was studied using a JEOL JSM-6610LV scanning electron microscope. RESULTS. The amount of siler at the level of 1mm from the apex in the group with the tug-back effect averaged 25.05%, and in the group without the tug-back effect – 30.9%. At the 3 mm level, these figures were 28.98% and 33.19%, respectively. The number of pores in teeth with a tug-back effect at the level of 1 mm was 10.5% of the circumference of the root filling, and in teeth without a tug-back – 19.4%. At the 3 mm level in teeth with tug-back – 4.7%, without tug-back – 12.4%. CONCLUSIONS. Presence of tug-back effect does not improve tightness of root channel apical part.